ENTRANCE RESISTANCE OF THE LIKE-PLAZMA TYPE ANISOTROPIC LAYER IN HARMONIOUS INFLUENCE MODE - V. F. Yanushkevich; E. Yu. Zayats; K. I. Kremenya (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis of an entrance impulse of an anisotropic layer of plazmapodobny type in the mode of harmonious influence is carried out. Consistent patterns of dielectric layer resistance change in the wide frequency and deep range are determined.